Enhance photoelectrochemical hydrogen-generation activity and stability of TiO2 nanorod arrays sensitized by PbS and CdS quantum dots under UV-visible light - Li, Lei (2015)
We develop a composite photoanode by sensitizing TiO 2 nanorod arrays with PbS quantum dots (QDs) and CdS QDs. Benefitted from additional introduced PbS QDs and CdS QDs onto TiO 2 , the absorption of the composite photoanodes are broaden from UV to visible region. The experimental results showed that the PbS sandwiched between TiO 2 and CdS cannot only broad the absorption properties but also improve the stability. The stability can be explained by the hole facile transmission from PbS to CdS because of the valence band offsets between PbS and CdS which cause a small energy barrier and reduce the hole accumulation. The photocurrent density reached 1.35 mA cm −2 at 0.9716 V vs. RHE (0 V vs. Ag/AgCl, under 60 mW cm −2 illumination) for TiO 2 /PbS/CdS. The highest photocurrent of TiO 2 /PbS/CdS can be explained by the smallest of total resistance (138 Ω cm −2 ) compared to TiO 2 /CdS and pristine TiO 2 .